The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s12016-009-8158-6
|View full text |Cite|
|
Sign up to set email alerts
|

Infectious Aspects and the Etiopathogenesis of Rheumatoid Arthritis

Abstract: Infections are believed to contribute to the maturation of the immune system from the innate to the adaptive phases and therefore may take part in the induction of autoimmune conditions. In the current study, we present an extensive analysis conducted on sera samples of patients with rheumatoid arthritis in order to seek evidence of previous or coexisting infectious processes using the Bio-Rad BioPlex immunoassay analyzer. We detected higher rates of serological evidence of infections with Epstein-Barr virus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Clinical and animal model studies have suggested that infections by many micro-organisms, such as Porphyromonas gingivalis (Bartold et al , 2010; Hitchon et al , 2010), Proteus mirabilis (Arabski et al , 2012), Epstein–Barr virus (Mourgues et al , 2016) and mycoplasma contribute to the aetiopathogenesis of RA (Durigon et al , 1993). Higher rates of serological evidence of infections with Epstein–Barr virus and cytomegalovirus were detected in RA patients than in population controls (Magnusson et al , 2010; Meron et al , 2010). …”
Section: Introductionmentioning
confidence: 91%
“…Clinical and animal model studies have suggested that infections by many micro-organisms, such as Porphyromonas gingivalis (Bartold et al , 2010; Hitchon et al , 2010), Proteus mirabilis (Arabski et al , 2012), Epstein–Barr virus (Mourgues et al , 2016) and mycoplasma contribute to the aetiopathogenesis of RA (Durigon et al , 1993). Higher rates of serological evidence of infections with Epstein–Barr virus and cytomegalovirus were detected in RA patients than in population controls (Magnusson et al , 2010; Meron et al , 2010). …”
Section: Introductionmentioning
confidence: 91%
“…Yamanishi et al [22] found increased IgM rheumatoid factor in B cells chronically stimulated with H. pylori urease. However, several studies demonstrated that there is a lower prevalence of H. pylori in RA patients, and other studies found the prevalence of H. pylori to be similar to that of the healthy controls [27,34,35] . After H. pylori eradication, no change in RA symptoms was reported by several studies [36][37][38] , although improvement was noted in others [39,40] .…”
Section: Rheumatoid Arthritismentioning
confidence: 97%
“…Sera from RA patients contain high titres of Epstein-Barr virus (EBV) antigens and of antibodies to latent and replicative EBV antigens. In addition, EBV RNA has been identified in B cells in synovial tissue from RA patients [35]. Despite these findings, the evidence that microorganisms are involved in the development of RA remains inconclusive.…”
Section: Infectionsmentioning
confidence: 99%